Polycystic Ovary Syndrome: Do Endocrine-Disrupting Chemicals Play a Role? - Barrett, Emily S.; Sobolewski, Marissa (Seminars in Reproductive Medicine, 2014)
Polycystic ovary syndrome (PCOS) is a heterogeneous disorder characterized by multiple endocrine disturbances, and its underlying causes, although uncertain, are likely to be both genetic and environmental. Recently, there has been interest in whether endocrine-disrupting chemicals (EDCs) in the environment, particularly Bisphenol A (BPA), may contribute to the disorder. In animal models, exposure to BPA during the perinatal period dramatically disrupts ovarian and reproductive function in females, often at doses similar to typical levels of human exposure. BPA also appears to have obesogenic properties, disrupting normal metabolic activity and making the body prone to overweight. In humans, cross-sectional data suggest that BPA concentrations are higher in women with PCOS than in reproductively healthy women, but the direction of causality has not been established. As this research is in its infancy, additional work is needed to understand the mechanisms by which EDCs may contribute to PCOS as well as the critical periods of exposure, which may even be transgenerational. Future research should also focus on translating the promising work in animal models into longitudinal human studies and determining whether additional EDCs, beyond BPA, may be important to consider.
Keywords: PCOS; Bisphenol A; BPA; Endocrine-disrupting chemicals; EDCs